Lipopeptide Nanoparticles: Development of Vaccines against Hookworm Parasite. Issue 10 (12th August 2015) - Fuaad, Abdullah A. H. Ahmad; Pearson, Mark S.; Pickering, Darren A.; Becker, Luke; Zhao, Guangzu; Loukas, Alex C.; Skwarczynski, Mariusz; Toth, Istvan
Abstract Necator americanus (hookworm) infects over half a billion people worldwide. Anthelminthic drugs are commonly used to treat the infection; however, vaccination is a more favorable strategy to combat this parasite. We designed new B‐cell peptide epitopes based on the aspartic protease of N. americanus (Na‐APR‐1). The peptides were conjugated to self‐adjuvanting lipid core peptide (LCP) systems via stepwise solid‐phase peptide synthesis (SPPS) and copper catalyst azide–alkyne cycloaddition (CuAAC) reactions. The LCP vaccine candidates were able to self‐assemble into nanoparticles, were administered to mice without the use of additional adjuvant, and generated antibodies that recognized the parent epitope. However, only one LCP derivative was able to produce a high titer of antibodies specific to Na‐APR‐1; circular dichroism analyses of this compound showed a β‐sheet conformation for the incorporated epitope. This study provides important insight in epitope and delivery system design for the development of a vaccine against hookworm infections.